2014
DOI: 10.1364/oe.22.014148
|View full text |Cite
|
Sign up to set email alerts
|

Near-field observation of light propagation in nanocoax waveguides

Abstract: We report the observation of propagating modes of visible and near infrared light in nanoscale coaxial (metal-dielectric-metal) structures, using near-field scanning optical microscopy. Together with numerical calculations, we show that the propagated modes have different nature depending on the excitation wavelength, i.e., plasmonic TE11 and TE21 modes in the near infrared and photonic TE31, TE41 and TM11 modes in the visible. Far field transmission out of the nanocoaxes is dominated by the superposition of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17] Among the different subwavelength structures that have been analyzed, the nanocoax is of particular interest, as this structure is considered to have high transmittance to visible light and is a promising structure for deep-subwavelength, low-loss propagation of plasmonic and photonic radiation modes at optical and infrared frequencies. 12,15,18 The nanocoax geometry already has been employed in a variety of applications including photovoltaic (PV) solar cells, optical nanoantennas, negative index materials, and light-emitting bers. [19][20][21][22][23][24] For example, the ability of a nanocoax to have its dielectric replaced with a semiconducting/PV material allows for the absorption or generation of light as it propagates along its axis, yet have photogenerated electrical current ow radially between the inner and outer metals.…”
Section: (1) Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Among the different subwavelength structures that have been analyzed, the nanocoax is of particular interest, as this structure is considered to have high transmittance to visible light and is a promising structure for deep-subwavelength, low-loss propagation of plasmonic and photonic radiation modes at optical and infrared frequencies. 12,15,18 The nanocoax geometry already has been employed in a variety of applications including photovoltaic (PV) solar cells, optical nanoantennas, negative index materials, and light-emitting bers. [19][20][21][22][23][24] For example, the ability of a nanocoax to have its dielectric replaced with a semiconducting/PV material allows for the absorption or generation of light as it propagates along its axis, yet have photogenerated electrical current ow radially between the inner and outer metals.…”
Section: (1) Introductionmentioning
confidence: 99%
“…The localization of applied light is also important when using minimum light intensities to mediate the behavior of a particular cell type, as light incident from above the neural assembly will scatter and attenuate upon entering the medium prior to being absorbed by the light-sensitive opsins. Ozden et al ( 2013 ) have previously shown peak intensity to be inversely proportional to stimulating optical fiber aperture diameter, and since the individual coaxes are capable of being fabricated at sub-cellular dimensions (Merlo et al, 2014 ) (~1 μm), the cNEA could provide a solution for lower power consumption as well as facilitating direct stimulation of an individual cell (or region within a cell). In contrast, when using macroscale optical fibers for such stimulation, the technical problems of tissue damage and unintentional illumination of distal neurons are unavoidable (Buzsáki et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, crosstalk between pixels of conventional devices with high spatial resolution is a consequence of their unshielded nature; a shielded coaxial device can suppress this limitation, uniquely allowing increases in pixel density. Also similar to that macroscale coax is the micro- and nanoscale version's ability to propagate subwavelength electromagnetic radiation, including visible light (Rybczynski et al, 2007 ; Merlo et al, 2014 ). Nanoscale coaxial arrays have been previously used by some of the present authors (Rizal et al, 2015 ) in a variety of biological (Archibald et al, 2015 ), chemical (Zhao et al, 2012 ; Rizal et al, 2013 ), optical (Rybczynski et al, 2007 ; Merlo et al, 2014 ) and photovoltaic (Naughton et al, 2010 ) devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of two concentric electrodes separated by a dielectric or an air gap. The nanocoax has demonstrated ultrasensitive chemical detection of volatile organic compounds (Zhao et al, 2012), and exhibited nanophotonic properties as a waveguide for visible light (Merlo et al, 2014; Rybczynski et al, 2007). Recently, nanocoaxial arrays demonstrated electrochemical sensing capabilities via the detection of the redox species ferrocenecarboxylic acid (FCA) (Rizal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%